PENGARUH INFLASI DAN SUKU BUNGA TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SUBSEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018 - 2022 - Christianti, Valentina; Surahman, Arif (Journal of Research and Publication Innovation, 2024)
The aim of this research is to determine the effect of inflation and interest rates on firm value in food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2018 - 2022. The method used in the research is a quantitative method by taking inflation anf interest rate data as well as financial report data of food and beverage sub-sector companies listed on the Indonesia Stock Exchange. The sample used in this research was 21 companies from 45 populations. The data analysis used is descriptive statistic analysis, panel data regression analysis, classic assumption test and hypothesis test. The research results show that partially inflation has no effect on firm value (PBV). This can be seen from the significant value of 0,1006 > 0,05 dan tstatistic -1,657180 < ttable 1,98177. Meanwhile, interest rate partially have an effect on firm value (PBV). This can be seen from the significant value of 0.0482 < 0,05 dan tstatistic 1.999992 > ttable 1,98177. Based on simultaneous test, inflation and interest rates have no effect on firm value (PBV), this can be seen from the significant value of 0,132529 > 0,05 dan fstatistic 2.061530 < ftable 3,93.